The Role of Banking in Empowering MSMEs: Peran Perbankan Dalam Pemberdayaan UMKM - Diah Sawitri; Winda Junarda (Experimental Student Experiences, 2022)
Micro, Small and Medium Enterprises (MSMEs) have established their credibility, especially after the financial and currency crisis hit the country. These crises show that the SMEs sector is a key sector of the economy with a lot of potential for job growth. In writing this time the purpose of conducting this research is to find out about the regulations for the development of small and medium enterprises as well as about the role of banking in empowering a business in the micro and medium sector, which uses the research method of micro and small enterprises whose laws have the intent and purpose to provide contribution to Indonesia's economic growth. Rules This law contains rules for small and slim companies. The most recent reference to this standard is in Presidential Decree (KEPRES) No. 99 of 1998, which discusses various types of small businesses and the growth of the small business sector. All forms of policy are required by law to almost always receive government assistance. to ensure that the initiative's guiding ideas will be understood by local residents and government representatives.